Predicting shear wave velocity from conventional well logs with deep and hybrid machine learning algorithms - Rajabi M. Meysam; Hazbeh O. Omid; Davoodi Sh. Shadfar; Wood D. A. David; Tehrani P. S. Pezhman Soltani; Ghorbani H. Hamzeh; Mehrad M. Mohammad; Mohamadian N. Nima; Rukavishnikov V. S. Valery Sergeevich; Radwan A. E. Ahmed (2023, 2023)
Title screen